Sulfonamides: Antiviral Strategy for Neglected Tropical Disease Virus - Dash, Rudra N.; Moharana, Alok Kumar; Subudhi, Bharat Bhusan (Current Organic Chemistry, 2020)
The viral infections are a threat to the health system around the globe. Although more than 60 antiviral drugs have been approved by the FDA, most of them are for the management of few viruses like HIV, Hepatitis and Influenza. There is no antiviral for many viruses including Dengue, Chikungunya and Japanese encephalitis. Many of these neglected viruses are increasingly becoming global pathogens. Lack of broad spectrum of action and the rapid rise of resistance and cross-resistance to existing antiviral have further increased the challenge of antiviral development. Sulfonamide, as a privileged scaffold, has been capitalized to develop several bioactive compounds and drugs. Accordingly, several reviews have been published in recent times on bioactive sulfonamides. However, there are not enough review reports of antiviral sulfonamides in the last five years. Sulfonamides scaffolds have received sufficient attention for the development of non- nucleoside antivirals following the emergence of cross-resistance to nucleoside inhibitors. Hybridization of bioactive pharmacophores with sulfonamides has been used as a strategy to develop sulfonamide antivirals. This review is an effort to analyze these attempts and evaluate their translational potential. Parameters including potency (IC50), toxicity (CC50) and selectivity (CC50/IC50) have been used in this report to suggest the potential of sulfonamide derivatives to progress further as antiviral. Since most of these antiviral properties are based on the in vitro results, the drug-likeness of molecules has been predicted to propose in vivo potential. The structure-activity relationship has been analyzed to encourage further optimization of antiviral properties.
Keywords: sulfonamide